Adsorption of Mn(II) ions from wastewater using activated carbon obtained from Birbira (Militia ferruginea) leaves (Global Journal of Science Frontier Research, 1969)
The adsorption of manganese (II) onto activated carbon derived from the leaf an indigenous Ethiopian plant, namely Birbira (Militia ferruginea), was investigated using flame atomic absorption spectrometer. The effects of contact time, adsorbent dose, Mn (II) initial concentration, pH and temperature were investigated. The maximum adsorption occurred after 2 hrs. There was 95.8% of Mn 2+ adsorption at pH of 4.0. The positive value of ΔH shows that the adsorption of manganese ions on the adsorbent is an endothermic process. The values of free energy ( ΔG) were negative. The decrease in ΔG value with increasing temperature reveals that adsorption of the ion on the adsorbent becomes favorable at higher temperature. The calculated value of ΔH is 16.05 kJmol -1 and ΔS is 99.13JK -1 mol -1 . The two theoretical adsorption isotherms, namely, Langmuir and Freundlich were used to describe the experimental results. The Freundlich adsorption isotherm best fits and adsorption capacity was calculated to be 3.41 mg of Mn (II) per g of adsorbent. The adsorption followed the first order kinetics and was found to be pH dependent being maximum at pH 4.0. Reuse of the desorbed bio-adsorbent is possible. The effect of foreign ions on the removal of Mn (II) has been investigated. The removal of Mn (II) from industrial wastewater sample was also tested and showed that more than 93% removal is possible. The results showed that activated carbon prepared from Birbira (Militia ferruginea) leaves can be used for the removal of Mn (II) from wastewater.
Keywords: Industrial wastewater; Manganese removal; adsorbent; Militia ferruginea; adsorption isotherm; kinetics of adsorption and flame atomic absorption spect